Printing Health: Revolutionizing Pharmaceuticals through 3D Innovation (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The influence of additive manufacturing has grown significantly in the last few years because of the rising awareness and need for customized pharmaceuticals, medical instruments, and equipment. With the innovation in three-dimensional printing (3D-Printing) technology providing a broad scope to explore the infinite dimensions in the pharmaceuticals field, 3D items of diverse geometries may be created. Cost-effectiveness and on-demand printing are two significant advantages of printed drugs over traditional drug production, as is the ability to create very complicated and sophisticated dose forms based on individual needs. This article discusses a few 3D printing processes useful for producing pharmaceuticals as well as how they may be applied to creating effective pharmacological and therapeutical dosage forms, demonstrating the viability of this printing technology for routine industrial production processes.The two main pharmaceutical application areas were covered in this article. First, drug delivery systems, including different medications like controlled release solid dosage form, more than one drug in the form of polypills, gastro-floating mechanism of drug, in the form of Oro dispersible drug, and printed microneedles, are the subject that has received the most research. Second, 3D-Printing contributed to the creation of pharmaceutical tools including drug-eluting devices and tools to help chemists dispense medication.